Structure-function analysis of the Escherichia coli GrpE heat shock protein. - Wu, B (1996)
We have isolated various missense mutations in the essential grpE gene of Escherichia coli based on the inability to propagate bacteriophage lambda. To better understand the biochemical mechanisms of GrpE action in various biological processes, six mutant proteins were overexpressed and purified. All of them, GrpE103, GrpE66, GrpE2/280, GrpE17, GrpE13a and GrpE25, have single amino acid substitutions located in highly conserved regions throughout the GrpE sequence. The biochemical defects of each mutant GrpE protein were identified by examining their abilities to: (i) support in vitro lambda DNA replication; (ii) stimulate the weak ATPase activity of DnaK; (iii) dimerize and oligomerize, as judged by glutaraldehyde crosslinking and HPLC size chromatography; (iv) interact with wild-type DnaK protein using either an ELISA assay, glutaraldehyde crosslinking or HPLC size chromatography. Our results suggest that GrpE can exist in a dimeric or oligomeric form, depending on its relative concentration, and that it dimerizes/oligomerizes through its N-terminal region, most likely through a computer predicted coiled-coil region. Analysis of several mutant GrpE proteins indicates that an oligomer of GrpE is the most active form that interacts stably with DnaK and that the interaction is vital for GrpE biological function. Our results also demonstrate that both the N-terminal and C-terminal regions are important for GrpE function in lambda DNA replication and its co-chaperone activity with DnaK.